2007
DOI: 10.1016/j.chroma.2007.08.039
|View full text |Cite
|
Sign up to set email alerts
|

Stir bar sorptive extraction of volatile compounds in vinegar: Validation study and comparison with solid phase microextraction

Abstract: Stir bar sorptive extraction was evaluated for analysing volatiles in vinegar. The procedure developed shows detection and quantitation limits, and linear ranges adequate for analysing this type of compounds. The accuracy obtained was close to 100%, with repeatability values lower than 13%. The extraction efficiency is inversely affected by the acetic acid content. Although the absolute areas decrease, the compound area/internal standard area ratio remains constant, so for quantitative analysis, the acetic aci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
43
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 94 publications
(54 citation statements)
references
References 20 publications
11
43
0
Order By: Relevance
“…The concentration of propionic acid of SAV ranged from 60.5 to 302.3 mgL −1 . The contents of butanoic acid (3.5-229 mgL −1 ), 3-methylbutanoic acid (13.4-48.0 mgL −1 ) and hexanoic acid (0.1-5.7 mgL −1 ) were close to those in sherry vinegar determined by GC-MS (Guerrero et al 2007). The other four organic acids were non-volatile, which were lactic acid, succinic acid, tartaric acid and citric acid.…”
Section: Organic Acid Analysissupporting
confidence: 60%
See 3 more Smart Citations
“…The concentration of propionic acid of SAV ranged from 60.5 to 302.3 mgL −1 . The contents of butanoic acid (3.5-229 mgL −1 ), 3-methylbutanoic acid (13.4-48.0 mgL −1 ) and hexanoic acid (0.1-5.7 mgL −1 ) were close to those in sherry vinegar determined by GC-MS (Guerrero et al 2007). The other four organic acids were non-volatile, which were lactic acid, succinic acid, tartaric acid and citric acid.…”
Section: Organic Acid Analysissupporting
confidence: 60%
“…The concentration of acetoin in SAV was 686.84-4036.59 mgL −1 . Similarly, it has been found ranged from 265.29 mgL −1 to 1326.9 mgL −1 in sherry vinegar and balsamic vinegar (Guerrero et al 2007). The content of phenylethyl alcohol in SAV ranged from 14.5 to 39.0 mgL −1 which was similar to sherry vinegar (Natera Marín et al 2002).…”
Section: Volatile Profile Of Vinegar Samplesmentioning
confidence: 78%
See 2 more Smart Citations
“…Three known ligands of D. melanogaster olfactory receptor neurons, acetoin, ethyl acetate, and 2-phenyl ethanol (Stensmyr et al 2003;Hallem and Carlson 2006;De Bruyne and Baker 2008), were also found in vinegar headspace (Table 2; Cocchi et al 2008;Guerrero et al 2007). They were tested as single compounds and in blends, at the release rate found in vinegar headspace.…”
Section: Attraction To Vinegar Headspace Volatiles and Synthetic Vinementioning
confidence: 97%